MEMAHAMI EKONOMI DIGITAL DI INDONESIA: STUDI KASUS MARKETPLACE - I Wayan Sukadana, Nurbetty Manik, (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2020)
The trade sector has a fairly high contribution to GDP is undergoing a transformation from conventional to digital (e-commerce), transactions that have been made online. The trade process is also easy because it can be done only through websites and applications, but this convenience also has shortcomings because competition from e-commerce is not only domestic products, but also products from abroad which have advantages over domestic products. This study is to determine the percentage of imported products traded in the Indonesian marketplace. The data in this study were taken from the ten largest marketplaces in Indonesia, namely Tokopedia, Bukalapak, Shopee, Lazada, Blibli, Jd, Qoo10, Elevenia, ILotte, and Kaskus. The time of data collection in this study was conducted in July 2019. The results of frequencies indicate that the percentage of imported products traded in the Indonesian marketplace is more than the local products traded in the Indonesian marketplace. Some of the advantages of imported products are logistics costs and low prices with a very easy import process.